Pengaruh Permainan Tradisional Petak Umpet terhadap Penyesuaian Sosial Anak Usia Sekolah Dasar - Valentina Mbadhi; Maria Finsensia Ansel; Agustina Pali (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The aim of the research was to find out the influence of traditional game hide-and-seek to the social adaptation of elementary students in RT 01 and 02 South Rewarangga. The method of the research was quantitative research. The sample was the elementary students of graden 4, 5 and 6 consist of 57 students through probability sampling whichc included in simple random sampling. The instruments used were questionnaire. The data were analyzed by using descriptive statistical technique, try out test including normality, linearity and regression test. The result included regression result Y= 49.739 + 0,498X, the significant score was 0,019 smaller than probability score 0,05, t obtain was 2,444 higher than the t table 2,026 and R Square was 0,139 or 13,9% whereas the rest was 86,1% influenced by other variables. In conclusion, there was a significant influence of the application of traditional game hide-and-seek towward elementary students social adaptation. Keywords: Traditional Games, Hide and Seek, Social Adaptation, Elementary School Students